2018
DOI: 10.1177/2050640618766926
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal fat accumulation in human colorectal tissue and its association with abdominal obesity and insulin resistance

Abstract: Background: In addition to visceral fat, peripheral ectopic fat accumulation is suggested to play a role in the pathophysiology of metabolic syndrome, which is known to be associated with not only cardiovascular diseases and type 2 diabetes mellitus but also colorectal cancer. Objective: This study aims to clarify whether there is ectopic fat accumulation in human colorectal tissue in association with metabolic syndrome or its components such as abdominal obesity and insulin resistance. Methods: Lipid contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Using GTEx’s histology data we were able to elucidate an association between ADIPOQ , a gene decreasing with age in multiple tissues, and loss of fat in the CLNTRN sub-mucosal space. Our findings are inconsistent with other literature stating that inter-mucosal fat increases with BMI [30] and does not decrease with age [31]. However our data differs from theirs in several regards.…”
Section: Discussioncontrasting
confidence: 99%
“…Using GTEx’s histology data we were able to elucidate an association between ADIPOQ , a gene decreasing with age in multiple tissues, and loss of fat in the CLNTRN sub-mucosal space. Our findings are inconsistent with other literature stating that inter-mucosal fat increases with BMI [30] and does not decrease with age [31]. However our data differs from theirs in several regards.…”
Section: Discussioncontrasting
confidence: 99%
“…Visceral fat can secrete tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1 and other proinflammatory factors to promote the onset and development of insulin resistance. 28 However, the VFA does not reflect fat accumulation in the liver, skeletal muscle, 29 submucosa of the intestinal wall, 30 or even astrocytes. 31 This ectopic fat accumulation can also lead to the development of insulin resistance and affect blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The grade of lipid droplet accumulation was significantly associated with BMI, waist circumference and visceral fat. This study showed the presence of submucosal fat accumulation in human colorectal tissue in association with abdominal obesity and insulin resistance [11]. It is important to note that systemic reviews and meta-analyses of studies involving several ethnic groups provide robust statistical evidence on the superiority of WHtR over waist circumference and BMI for detecting cardiometabolic risk factors in both genders [26–28].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to directly visualize the submucosa with advanced endoscopic techniques has facilitated the analysis of submucosal fatty tissue and its possible relationship with metabolic syndrome or its components such as abdominal obesity. Despite this, there are still limited descriptions of this phenomenon in the endoscopic literature [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%